2022
DOI: 10.3389/fpubh.2021.736948
|View full text |Cite
|
Sign up to set email alerts
|

People Who Die by Suicide Without Receiving Mental Health Services: A Systematic Review

Abstract: IntroductionThe majority of people who die by suicide have never seen a mental health professional or been diagnosed with a mental illness. To date, this majority group has largely been ignored, with most existing research focusing on predictors of suicide such as past suicide attempts. Identifying the characteristics of people who die by suicide without receiving services, often with a fatal first attempt, is crucial to reduce suicide rates through guiding improvements to service pathways and “just in time” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 101 publications
(195 reference statements)
2
28
0
Order By: Relevance
“…Relative to people with known MH concerns, respondents who endorsed SI that was not accompanied by diagnosed mental health concern(s) were more likely to be male and non-White, and less likely to be medically vulnerable toward COVID-19 infection or unemployed. These results align with recent meta-analytic findings that people who died by suicide without receiving mental health services were more likely to be male, younger or older (vs. middle) aged, ethnic minorities, and living in rural communities ( Tang et al, 2021 ; Walby et al, 2018 ). Such findings underscore the importance of developing varied, culturally sensitive supports to effectively reach and engage people who may be at risk.…”
Section: Discussionsupporting
confidence: 90%
“…Relative to people with known MH concerns, respondents who endorsed SI that was not accompanied by diagnosed mental health concern(s) were more likely to be male and non-White, and less likely to be medically vulnerable toward COVID-19 infection or unemployed. These results align with recent meta-analytic findings that people who died by suicide without receiving mental health services were more likely to be male, younger or older (vs. middle) aged, ethnic minorities, and living in rural communities ( Tang et al, 2021 ; Walby et al, 2018 ). Such findings underscore the importance of developing varied, culturally sensitive supports to effectively reach and engage people who may be at risk.…”
Section: Discussionsupporting
confidence: 90%
“…However, the ‘under the radar’ men are difficult to reach by the very nature of their experiences. Connecting with men in innovative and non-stigmatising ways, through a variety of non-health settings such as workplaces, schools, social welfare agencies, cultural organisations and social media is needed [ 10 ]. As participant P1 described earlier in this paper, there is currently a greater community response to the needs of young people impacted by tragedy, abuse and trauma than ever before.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of this larger project, Black Dog conducted a systematic review of the published literature examining predictors of dying by suicide without having received professional help. Key risk factors were identified for being under the radar: male sex, both younger and older age, rural location and the absence of a mental health diagnosis [ 10 ]. In the second phase, Black Dog surveyed 415 men and interviewed 37 men experiencing suicidal thoughts and/or behaviours to examine their views toward health services and family members and to understand coping styles and preferences for service provision.…”
Section: Introductionmentioning
confidence: 99%
“…Second, older adults with mental health/substance misuse/addiction problems should be helped to access appropriate mental health and/or substance use treatment. A recent systematic review showed that suicide decedents who were men, under 25 years or 65 years and older, racial/ethnic minorities, residents in rural areas, and experienced stressors and used violent means of suicide were less likely to have received mental health services ( Tang et al, 2022 ). Untreated depression in late life, especially among older adults with physical health problems and disability, has been associated with increased and persisting depressive symptom trajectories, further deterioration of physical function and cognitive health, and increased mortality ( Andreescu et al, 2008 ; Kaup et al, 2016 ; Mirza et al, 2016 ; Agustini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%